Combined Magnetic Nanoparticle‐based MicroRNA and Hyperthermia Therapy to Enhance Apoptosis in Brain Cancer Cells. Issue 20 (20th June 2014) - Yin, Perry T.; Shah, Birju P.; Lee, Ki‐Bum
<x xml:space="preserve">Abstract</x> A novel therapy is demonstrated utilizing magnetic nanoparticles for the dual purpose of delivering microRNA and inducing magnetic hyperthermia. In particular, the combination of lethal‐7a microRNA (let‐7a), which targets a number of the survival pathways that typically limit the effectiveness of hyperthermia, with magnetic hyperthermia greatly enhances apoptosis in brain cancer cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>